Effect of Origanum syriacum L. Essential Oil on the Storage Stability of Cooked Chicken Meat - Al-Hijazeen,M (2019)
ABSTRACT The effects of the addition of Origanum syriacum L. essential oil (OE) on the lipid and protein oxidation, and sensory attributes of cooked chicken meat were compared with those of synthetic commercial meat preservatives. Ground deboned and skinless chicken breast and thigh meat were distributed according to six treatments: (T1) control (no addition of meat preservative); or the addition of (T2) 100 ppm OE; (T3) 150 ppm OE; (T4) 300 ppm L-ascorbic acid (E-300); (T5) 5 and 14 ppm butylated hydroxyanisoleadded to breast and thigh meat, respectively, (BHA/E-320); and (T6) 150 ppm sodium nitrite (E-250). Meat samples were cooked and analyzed for lipid oxidation (TBARS levels) and protein oxidation (carbonyl levels) on days 0, 4, and 7 days of storage. In addition, cooked meat thigh patties were evaluated for cooking loss and sensory attributes. All additives were showed significant lipid and protein antioxidant effects (p<0.05) compared with the control treatment during storage, with the strongest effects obtained with OEat 150 ppm and E-250. Cooking loss was not influenced (p>0.05) by the treatments. The best sensory attribute scores were obtained with OEat 150 ppm and E-250 treatments. L-ascorbic acid and BHA also showed significant effect (p<0.05) on both lipid and protein oxidation values, and sensory attributes. Based on the results study, it concluded that OEat 150 ppm may be used in replacement of synthetic antioxidants to improve the storage stability of chicken meat.